Corrective feedback episodes in oral interaction: A comparison of a CLIL and an EFL classroom - Milla, Ruth; García Mayo, Maria Pilar (International Journal of English Studies, 2014)
This paper addresses the issue of corrective feedback (CF), a topic widely investigated in the last few decades (Sheen, 2011), and instructional context. We observed and recorded the oral interaction of an intact class of thirty Spanish intermediate-level high-school learners and two teachers in two settings: a traditional form-oriented English as a Foreign Language (EFL) classroom and a meaning-oriented Content and Language Integrated Learning (CLIL) classroom (Dalton-Puffer, 2011). Corrective feedback episodes (CFE; Lyster, 1994) were used as the unit of analysis. The findings of the study indicate that there are differences in the type, quantity and manner of CFE between the two learning contexts. Although no significant difference in the proportion of learners’ uptake was found between the EFL and CLIL contexts, a qualitative analysis of the data indicated that the teachers’ attitude toward CF influenced subsequent learner uptake. Implications for further research on CF, learner uptake and instructional context are suggested. doi: http://dx.doi.org/10.6018/ijes/14/1/151841